WEB-BASED SYLLABLE READING LEARNING MEDIA (BASUKA) FOR BEGINNING READING FOR SLOW LEARNER STUDENTS AT ELEMENTARY SCHOOL LEVEL - Suci Noor Rahmawaty; Ravik Karsidi; Joko Yuwono (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2023)
Based on previous research and preliminary studies that have been carried out by researchers, to assist teachers in teaching beginning reading and for students in addition to beginning reading practice, researchers are interested in developing learning media combined with the beginning reading method, namely the syllabic method. This media is named